Potret Laki-Laki Minangkabau dalam Naskah Drama Sabai Nan Aluih Karya Wisran Hadi - David Agustian; Nurizzati Nurizzati (Persona: Kajian Bahasa dan Sastra, 2023)
The existence of Minangkabau culture, language and oral literature seems to have started to change from time to time. This is due to the extraordinary influence of the times that is felt by the younger generation. The portrait of Minangkabau men in the Sabai Nan Aluih manuscript by Wisran Hadi contains meaning and life lessons that can be taken, one of which is that the role of men in Minangkabau must have principles in deciding issues so that there is no confusion. The aims of this research are, (1 ) The roles of the characters in the drama script Sabai Nan Aluih by Wisran Hadi, (2) The characters in the drama script Sabai Nan Aluih by Wisran Hadi, (3) Portraits of Minangkabau men in the drama script Sabai Nan Aluih by Wisran Hadi. The type of research used is literary research using descriptive analytical methods. This kind of research technique in literary criticism is called descriptive qualitative. The data source for this research is the drama script Sabai Nan Aluih by Wisran Hadi published by Balai Pustaka 1982. The research instrument is the researcher himself as the main instrument who sees, reads, understands, identifies, and records matters relating to the portrait of the Kaba Man in Manuscript of Sabai Nan Aluih by Wisran Hadi. The results of the study show that (1) the character who plays a role in the drama script of Sabai Nan Aluih is Rajo Babandiang who is none other than the father of Sabai Nan Aluih, (2) the characters that stand out in the story of this drama script are: (a) firm, ( b) wise, (c) compassionate, (d) arrogant, (e) cowardly, (3) portraits of Minangkabau male figures which can be interpreted in this study are in their positions as penghulu/mother, as father, and as urang sumando .